Exploration of Whitefly (Bemisia tabaci) (Homoptera: Aleyrodidae) on Tomato (Solanum lycopersicum Mill) in Kedisan Village, Kintamani District, Bangli Regency - I Wayan Diksa Gargita; Isto Umbi Maramba Jua; I Wayan Dirgayana (Universitas Dwijendra Press, 2023)
The main pest of tomato plants is the whitefly Bemisia tabaci (Homoptera: Aleyrodidae). This study aims to determine the symptoms of attack, population size and percentage of attack by B. tabaci on tomato plants in Kedisan Village, Kintamani District, Bangli Regency, Bali. The research was conducted from January to March 2023 in Kedisan Village, Kintamani District, Bangli Regency. This research was carried out using a direct survey method with direct observation in the field. Sampling was carried out by purposive sampling using the diagonal sampling method with 10 sample points and 3 plant clusters were taken at each sampling point so that a total of 30 plant families were observed. The variables observed were attack symptoms, population size and percentage of B. tabaci attack on tomato plants. The data obtained were analyzed and presented in the form of tables and graphs. The results showed that B. tabaci was found on tomato plants in the farmers fields in Kedisan village. Symptoms of B. tabaci attack on tomato plants are necrotic spots and chlorosis on leaves, which are caused by damage to leaf cells and tissues due to attack by nymphs and adult insects. Pests began to be found at 14 DAP (Day after Planting) with an average of 0.37 individuals/plant and the highest population was found at 63 DAP with an average of 1.63 individuals/plant on tomato plants. The results of the analysis show that the high percentage of attacks occurred at 63 DAP of 93.33%. In general, the high number of pest populations affects the high pest attacks as evidenced by the high percentage of B. tabaci attacks.